2020
DOI: 10.2147/jpr.s244787
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Efficacy and Safety of Paravertebral Block Combined with Parecoxib During Video-Assisted Thoracic Surgery: A Randomized Controlled Trial</p>

Abstract: Background: Although video-assisted thoracoscopic surgery (VATS) is increasingly used, the optimal analgesia strategy is still unknown. We explore the efficacy and safety of preemptive ultrasound-guided paravertebral block (PVB) combined with parecoxib during VATS. Methods: Seventy-four patients were divided into two groups. PVBs were performed before anesthesia induction under real-time ultrasound guidance. Visual analog scale (VAS) score with coughing at 48 h after surgery, postoperative sufentanil consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…It inhibits the aggregation of leukocytes, reduces the formation of bradykinin, inhibits platelet agglutination, and induces apoptosis and anti-angiogenesis by selectively inhibiting the activity of COX-2, thus producing antipyretic, analgesic, anti-inflammatory, and anti-cancer effects ( Kaduševičius, 2021 ). Studies have shown that in major surgeries such as thoracic surgery and orthopedics, parecoxib sodium can reduce pain levels and postoperative serum inflammatory factor levels, reduce the incidence of adverse reactions such as nausea and vomiting and pulmonary infections, reduce analgesic drug consumption, reduce hemodynamic instability, and reduce surgery-related stress reactions ( Yang et al, 2020 ; Li et al, 2022a ). Basic research has revealed that parecoxib sodium can exert neuroprotective effects by inhibiting and improving mitochondrial dysfunction in the substantia nigra via the COX-2/PGE2 pathway ( Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits the aggregation of leukocytes, reduces the formation of bradykinin, inhibits platelet agglutination, and induces apoptosis and anti-angiogenesis by selectively inhibiting the activity of COX-2, thus producing antipyretic, analgesic, anti-inflammatory, and anti-cancer effects ( Kaduševičius, 2021 ). Studies have shown that in major surgeries such as thoracic surgery and orthopedics, parecoxib sodium can reduce pain levels and postoperative serum inflammatory factor levels, reduce the incidence of adverse reactions such as nausea and vomiting and pulmonary infections, reduce analgesic drug consumption, reduce hemodynamic instability, and reduce surgery-related stress reactions ( Yang et al, 2020 ; Li et al, 2022a ). Basic research has revealed that parecoxib sodium can exert neuroprotective effects by inhibiting and improving mitochondrial dysfunction in the substantia nigra via the COX-2/PGE2 pathway ( Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The local anesthetic blocks the somatic and sympathetic nerve supply of the dermatome of interest thereby providing postsurgical analgesia[ 27 ]. Its efficacy has been tested in a randomized setting by numerous authors not only for breast surgery but also for thoracic surgeries[ 12 , 28 ]. However, one important limitation of nerve blocks, in general, is the short duration of action of the local anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…There are many definitions of CPSP, although we defined CPSP as pain at the surgical site (NRS score ≥ 1) that the patient was identified as being related to the surgery, according to previous high-quality studies. [10,16,17]…”
Section: Methodsmentioning
confidence: 99%